Aberrant localization and underglycosylation of highly accumulating single-chain Fv-Fc antibodies in transgenic arabidopsis seeds - Van Droogenbroeck, Bart; Colanesi, Sarah; Hillmer, Stefan; Robinson, David G. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
Production of high-value recombinant proteins in transgenic seeds is an attractive and economically feasible alternative to conventional systems based on mammalian cells and bacteria. In contrast to leaves, seeds allow high-level accumulation of recombinant proteins in a relatively small volume and a stable environment. We demonstrate that single-chain variable fragment (scFv)-Fc antibodies, with N-terminal signal sequence and C-terminal KDEL tag, can accumulate to very high levels as bivalent IgG-like antibodies in Arabidopsis thaliana seeds and illustrate that a plant-produced anti-hepatitis A virus scFv-Fc has similar antigen-binding and in vitro neutralizing activities as the corresponding full-length IgG. As expected, most scFv-Fc produced in seeds contained only oligomannose-type N-glycans, but, unexpectedly, 35-40% was never glycosylated. A portion of the scFv-Fc was found in endoplasmic reticulum (ER)-derived compartments delimited by ribosome-associated membranes. Additionally, consistent with the glycosylation data, large amounts of the recombinant protein were deposited in the periplasmic space, implying a direct transport from the ER to the periplasmic space between the plasma membrane and the cell wall. Aberrant localization of the ER chaperones calreticulin and binding protein (BiP) and the endogenous seed storage protein cruciferin in the periplasmic space suggests that overproduction of recombinant scFv-Fc disturbs normal ER retention and protein-sorting mechanisms in the secretory pathway.